Healing outcomes of single-visit endodontic therapy versus combined endo-perio therapy in grade II furcation involvement - Anamika Anamika (Bioinformation, 2026)
Grade II furcation involvement with endo-periodontal lesions is a complex clinical problem. Therefore, it is of interest to examine the healing of single-visit endodontic therapy and combined endodontic periodontal therapy in Grade II furcation involvement. Hence, 80 patients who were treated by single-visit root canal therapy and endodontically followed by periodontal debridement and regenerative procedures. Clinical parameters like probing pocket depth, clinical attachment level and tooth mobility were evaluated. Thus, data shows the combined endodontic–periodontal therapy provides significantly better healing outcomes than single-visit endodontic treatment.